PENGARUH PROFITABILITAS DAN LIKUIDITAS TERHADAP STRUKTUR MODAL PERUSAHAAN ASURANSI ( Yang terdaftar di Bursa Efek Indonesia (BEI) periode 2012-2014 ) - Thomi irvan; Lena Farida (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
The purpose of this study was to investigate the profitability and liquidity to the capital structure companies. This study focused on insurance companies listed in Indonesia Stock Exchange (IDX) for period 2012-2014. The data used in this research is secondary data, financial highlights (annual report) and performance summary. This study used purposive sampling method in order to collect the sample. Analysis of data using multiple linear regression analysis with SPSS 20.The results showed that the profitability and liquidity simultaneously not significantly affect the capital structure . The coefficient of determination that has been adjusted by 56.9 % . it can be concluded that the profitability and liquidity does not affect 56.9 % . While 43.1 % are influenced by other factors not included in this study , such as the size of the company , the stability of sales , operating leverage , growth rates and taxes.Keywords : Profitability, Liquidity and capital structure